In silico analysis of overall survival with YBX1 in male and female solid tumours - Marignol, Laure; Robert Grimes, David (My University, 2024)
The Y-box binding protein-1 (YBX1) gene codes for a multifunctional oncoprotein that is increasingly being linked to the regulations of many aspects of cancer cell biology. Disparities in treatment outcomes between male and female cancer patients are increasingly reported. This study aimed to examine the relationship between YBX1 expression and overall survival in male and female patients with solid tumours. Overall survival and YBX1 expression data for cohorts of male and female cancer patients obtained from freely available databases were analysed with a cox proportional hazard model with covariates of biological sex and YBX1 expression. Kaplan–Meier curves and Violin plots were constructed for segregated male and female cohorts. High YBX1 expression was significantly associated with poor survival in 2 female-only and 4 mixed-sex cancer sites. In female lung cancer patients, better survival and lower YBX1 expression were identified. The clinical importance of YBX1 expression in cancer ought to be evaluated in a sex-specific manner, especially in lung cancer.
PUBLISHED
cited By 0
Keywords: cancer; Y-box binding protein-1 (YBX1) gene codes; male and female patients; Biological sex; Survival; cancer; Y-box binding protein-1 (YBX1) gene codes; male and female patients